Advantage of dual-confined plasmas over conventional and facing-target plasmas for improving transparent-conductive properties in Al doped ZnO thin films - Long Wen (2018)
© 2015 Elsevier B.V. Al doped ZnO films are prepared in dual-confined plasmas (rectangular side-ways and one top-side) in DC magnetron sputtering system without intentional substrate-heating. Present confinement shows improved transparent-conductive properties in Al doped ZnO thin films, when compared to those of deposited by conventional and facing-target confinement. As a function of working pressure and power density, plasma diagnostics is carried out at substrate location using optical emission spectroscopy, thermal energy transfer and net current density measurements. The optical, and electrical properties of the synthesis AZO films were studied and correlated to plasma conditions. It is found that high electron temperature, higher plasma density and highly ionization of oxygen play a key role in enhancing the deposition rate and transmittance ~90% along with minimizing resistivity in the order of 10-4Ωcm.